Coping With Constraints: Achieving Effective Conservation With Limited Resources - Walls, Susan C. (Frontiers in Ecology and Evolution, 2018)
Conservation resources have become increasingly limited and, along with social, cultural and political complexities, this shortfall frequently challenges effectiveness in conservation. Because conservation can be costly, efforts are often only initiated after a species has declined below a critical threshold and/or when statutory protection is mandated. However, implementing conservation proactively, rather than reactively, is predicted to be less costly and to decrease a species' risk of extinction. Despite these benefits, I document that the number of studies that have implemented proactive conservation around the world are far fewer than those that simply acknowledge the need for such action. I provide examples of proactive actions that can ameliorate shortfalls in funding and other assets, thus helping conservation practitioners and managers cope with the constraints that resource limitation imposes. Not all of these options are new; however, the timing of their implementation is critical for effective conservation, and the need for more proactive conservation is increasingly recognized. These actions are (1) strengthening and diversifying stakeholder involvement in conservation projects; (2) complementing time-consuming and labor-intensive demographic studies with alternative approaches of detecting declines and estimating extinction risk; and (3) minimizing future costly conservation and management by proactively keeping common species common. These approaches may not constitute a cure-all for every conservation crisis. However, given escalating rates of species' losses, perhaps a reminder that these proactive actions can reduce conservation costs, save time, and potentially thwart population declines is warranted.